Germany 2007: Undiminished High Construction Production and Increased Construction Prices - Bernd Bartholmai; Martin Gornig (Weekly Report, 2007)
After the high growth of 2006, the first quarter of 2007 also shows undiminished high construction production. Evidence of this is provided by the number of hours worked, which see growth rates in double figures in all fields of civil and structural engineering; yet it is surprising that growth in industrial construction lagged somewhat. It remains to be seen to what extent the extremely strong increase in the performance of the construction industry reflects demand or simply consistently favourable weather conditions, for there was actually no real winter in the two quarters preceding and following the new year. Data on the finishing industry in the first quarter indicates a lower dynamics - the number of hours worked increased by almost 8%, compared with 24% in the construction industry. This means that the demand for construction work and services related to existing buildings, particularly in housing construction, is not continuing at the high level last achieved.
Keywords: L74; O11; 330; Housing demand; Construction industry; Forecast 2007